Control of Maximum Power Point Tracking for Stand-Alone Photovoltaic System Using Voltage Comparison Technique - Jamri , Mohd Saifuzam; Anuar , Mohamed Kassim (2013)
This paper proposed the other method to control of maximum power point tracker for stand- alone photovoltaic system using closed-loop voltage mode control algorithm. Approach: The PV module was modeled based on the parameters obtained from a commercial PV data sheet while voltage mode control was modeled using simulink block model. A DC-DC boost converter was chosen to regulate the DC voltage from the PV module. The voltage mode control maximum power point tracking model was simulated under a constant and a variable change of solar irradiance and temperature. The perturb and observe maximum power point tracker model was developed and compared with this proposed method in order to validate the performance of output results. Results: Results showed that the voltage mode control maximum power point tracking model yields the similar performance as produced by the photovoltaic system controlled by perturb and observe maximum power point tracking algorithm simulation in terms of the voltage, current and power generated under the changing irradiant and temperature condition. Conclusion/Recommendations: The voltage mode control technique is possible to be implemented which yields the similar performance as the results from conventional MPPT method.